Casimir force phase transitions in the graphene family - Pablo Rodriguez-Lopez (Nature Portfolio, 2017)
The Casimir force is a ubiquitous interaction arising from electromagnetic quantum fluctuations. Here, the authors uncover the underlying physics governing Casimir force phase transitions in staggered 2D materials in the graphene family.